MONTE CARLO SIMULATION IN ESTIMATING CLEAN WATER SUPPLIES - Fajari Husnul Walid; Sajaratud Dur; Rima Aprilia (Journal of Mathematics and Scientific Computing With Applications, 2021)
Estimates are important tools in effective and efficient planning for predictingfuture events. Identical estimates of the future values of a variable for planningor decision making of a situation to estimate future values. Monte Carlosimulation is a simulation model that involves a series of random and samplingwith a probability distribution that can be known and determined, then thissimulation can be used. In this study, data is taken from the amount of waterusage in PDAM Tirtanadi H.M branch. Yamin, North Sumatra from January2018 to June 2019. Then, the data is processed and analyzed using MonteCarlo Simulation to determine the forecast results in the years that follow. Theresult is an estimated amount of water usage in 2019 and 2020 at PDAMTirtanadi H.M branch. Yamin, North Sumatra is 8,604,556 and 8,592,873. The estimated amount of water use is down from the amount of water use in2018 which reached 8,685,356. The amo